2023
DOI: 10.1093/braincomms/fcad057
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phosphorylated tau 217 in preclinical Alzheimer’s disease

Abstract: An accurate blood test for Alzheimer’s disease that is sensitive to preclinical proteinopathy and cognitive decline has clear implications for early detection and secondary prevention. We assessed the performance of plasma phosphorylated tau 217 (pTau217) against brain PET markers of amyloid ([11C]-labeled Pittsburgh compound B (PiB)) and tau ([18F]MK-6240), and its utility for predicting longitudinal cognition. Samples were analyzed from a subset of participants with up to 8 years follow-up in the Wisconsin R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Whilst previous studies have shown good biomarker accuracies for plasma p-tau217 17,20 , performances among CU participants in population-based cohorts have been scanty and in the few available papers the results have been less consistent 6,12,34 . This can be mainly attributable to the weak analytical performance (e.g., lack of quantifiable signals, poor precision) of first-generation p-tau217 assays in individuals with very low concentrations including CU participants and those in early symptomatic stages 2,3 .…”
Section: Discussionmentioning
confidence: 91%
“…Whilst previous studies have shown good biomarker accuracies for plasma p-tau217 17,20 , performances among CU participants in population-based cohorts have been scanty and in the few available papers the results have been less consistent 6,12,34 . This can be mainly attributable to the weak analytical performance (e.g., lack of quantifiable signals, poor precision) of first-generation p-tau217 assays in individuals with very low concentrations including CU participants and those in early symptomatic stages 2,3 .…”
Section: Discussionmentioning
confidence: 91%
“…Notably, p-tau217 exhibits larger-fold changes compared with p-tau181 and p-tau231, often achieving high discrimination, with areas under the curve (AUC) exceeding 90% . Additionally, p-tau217 demonstrates a unique longitudinal trajectory, showing increases associated with worsening brain atrophy and declining cognitive performance in individuals with elevated Aβ pathology …”
Section: Introductionmentioning
confidence: 99%
“…19,23 Additionally, p-tau217 demonstrates a unique longitudinal trajectory, showing increases associated with worsening brain atrophy and declining cognitive performance in individuals with elevated Aβ pathology. 24,25 With the imminent implementation of anti-Aβ therapies in dementia management, validated blood biomarkers are urgently needed to guide timely treatment decisions. While plasma p-tau217 has shown promise as a diagnostic tool for AD, its widespread evaluation has been hindered by limited availability of commercial assays.…”
mentioning
confidence: 99%
“…The most important recent advance in diagnostics for Alzheimer's disease (AD) has been the development of ultrasensitive plasma biomarker assays. Prior publications have assessed the ability of plasma [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] or amyloid positron emission tomography (PET) [18][19][20][21][22] to predict continuous cognitive decline or categorical clinical progression.…”
Section: Introductionmentioning
confidence: 99%